2015
DOI: 10.1016/j.biomaterials.2015.02.082
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle formulation of ormeloxifene for pancreatic cancer

Abstract: Pancreatic cancer is the fourth most prevalent cancer with about an 85% mortality rate; thus, an utmost need exists to discover new therapeutic modalities that would enhance therapy outcomes of this disease with minimal or no side effects. Ormeloxifene (ORM), a synthetic molecule, has exhibited potent anti-cancer effects through inhibition of important oncogenic and proliferation signaling pathways. However, the anti-cancer efficacy of ORM can be further improved by developing its nanoformulation, which will a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 68 publications
2
26
0
1
Order By: Relevance
“…The composition of SPION and SPION-Dtxl was evaluated using FTIR (Perkin Elmer Series Spectra 100, Waltham, MA) to affirm the drug encapsulation [37]. A Rigaku D/Max-B diffractometer (Rigaku Americas Corporation, The Woodlands, TX) was used to determine the crystalline behavior of SPION/SPION-Dtxl [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of SPION and SPION-Dtxl was evaluated using FTIR (Perkin Elmer Series Spectra 100, Waltham, MA) to affirm the drug encapsulation [37]. A Rigaku D/Max-B diffractometer (Rigaku Americas Corporation, The Woodlands, TX) was used to determine the crystalline behavior of SPION/SPION-Dtxl [26].…”
Section: Methodsmentioning
confidence: 99%
“…A Rigaku D/Max-B diffractometer (Rigaku Americas Corporation, The Woodlands, TX) was used to determine the crystalline behavior of SPION/SPION-Dtxl [26]. The thermal behavior of SPION and SPION-Dtxl was assessed using a Perkin Elmer Simultaneous Thermal Analyzer STA6000 [37]. …”
Section: Methodsmentioning
confidence: 99%
“…In keeping with this concept, it can be argued that while depleting stroma in a tumor will result in relieving the interstitial pressure on the blood vessels and promote drug delivery to the tumor, the tumor cells need to be obliterated as well in order to prevent their extravasation and spread to a distant location. This hypothesis is supported by a recent publication on two experimental drugs: one of the studies published in 2015, showed that ormeloxifene, a non-hormonal, non-steroidal oral contraceptive to be effective in reducing desmoplasia as well as induce tumor cell death in pancreatic cancer 19–21 . The other study, also from 2015, evaluated a water-soluble diterpene triepoxide, Minnelide against both patient tumor derived xenografts as well as the spontaneous KPC model for pancreatic cancer.…”
Section: Stroma As a Physical Barrier To Drug Deliverymentioning
confidence: 87%
“…Colony formation assay was performed to investigate the effect of miR-145-MNPF on the colony forming ability of pancreatic cancer cells, as described previously 15 . Briefly, HPAF-II and AsPC-1 cells were transfected with MNPF, NC-MNPF and miR-145-MNPF.…”
Section: Methodsmentioning
confidence: 99%